Possibilities and challenges for the promotion of observation stages in teaching training: from describing to analyzing-problematizing-interving - Pontes, Joyce Aparecida Soares de; Buriti, Maria Marta dos Santos (Revista Ensino de Geografia (Recife), 2021)
Insofar as it proposes to analyze the relationship between society and nature and its dimensions in the geographical space, Geography constitutes itself as a fundamental Discipline for the formation of critical and reflective citizens, aware of their role in the world and in their place of experience. In order to fulfill this purpose, in addition to being able to overcome the structural problems of public school education, it is essential that the contexts of teacher education are propositional to problematize and understand school reality in its multiple and contradictory faces, which is made possible through the dialectical combination of theoretical-scientific and practical knowledge. This implies, among other issues, rethinking the supervised internships that, more than a moment to live-describe the school, must be constituted as a moment to analyze it, problematize it and intervene positively in it. Taking this framework into account, the objective here is to analyze the possibilities and challenges for the dynamization of the observation stage, starting from the practical experiences and theoretical-reflective activities developed according to the formative assumptions worked in the Supervised Internship Curricular Component in Geography I, which is part of the curriculum of the Full Degree Course in Geography from the University State of Paraíba.